2018
DOI: 10.3389/fmicb.2017.02707
|View full text |Cite
|
Sign up to set email alerts
|

Bile-Salt-Hydrolases from the Probiotic Strain Lactobacillus johnsonii La1 Mediate Anti-giardial Activity in Vitro and in Vivo

Abstract: Giardia duodenalis (syn. G. lamblia, G. intestinalis) is the protozoan parasite responsible for giardiasis, the most common and widely spread intestinal parasitic disease worldwide, affecting both humans and animals. After cysts ingestion (through either contaminated food or water), Giardia excysts in the upper intestinal tract to release replicating trophozoites that are responsible for the production of symptoms. In the gut, Giardia cohabits with the host's microbiota, and several studies have revealed the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 68 publications
1
48
0
Order By: Relevance
“…Especially, the markedly higher proportion of Lactobacillus genus in the PXR-CAR-double null mice consistently correspond to a markedly decrease in major T-BAs in feces. Many species and strains of the Lactobacillus genus carry BSH that deconjugates the taurine and glycine molecules from BAs [68,69,[90][91][92][93][94][95]; in mice, the predominant effect is expected to be T-BA deconjugation, because taurine conjugation is a predominant pathway in mice over glycine conjugation.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, the markedly higher proportion of Lactobacillus genus in the PXR-CAR-double null mice consistently correspond to a markedly decrease in major T-BAs in feces. Many species and strains of the Lactobacillus genus carry BSH that deconjugates the taurine and glycine molecules from BAs [68,69,[90][91][92][93][94][95]; in mice, the predominant effect is expected to be T-BA deconjugation, because taurine conjugation is a predominant pathway in mice over glycine conjugation.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility to Giardia infection varies significantly among different age groups in humans and in animal models, which is likely due at least in part to age-related shifts in microbiota composition, as well as changes in host immune factors. Several studies have shown the efficacy of using a suckling mouse model to study infection with Giardia isolates that do not typically infect adult mice ( Hill et al, 1983 ; Allain et al, 2017 , 2018a ; Riba et al, 2020 ). Shifts in the microbiota that occur upon weaning may be responsible for this increased resistance to Giardia infection ( Hill et al, 1983 ).…”
Section: Role Of the Microbiome In Giardia Pathogementioning
confidence: 99%
“…Microbiome-encoded BSHs and secondary bile acid metabolism are associated with colonization resistance against pathogens such as Clostridioides difficile , which can use taurocholate (TCA) as a spore germinant, but vegetative cells are sensitive to most secondary bile acids [30]. Similarly, Lactobacillus johnsonii BSH activity has been shown to limit the eukaryotic pathogen Giardia duodenalis in vivo [31]. The variety of functions that BSH activity provides is unique to the biology of each organism and the niche it inhabits throughout the GIT, therefore warranting a better understanding of their utility for shaping the microbiota.…”
Section: Introductionmentioning
confidence: 99%